2018
DOI: 10.1007/978-3-319-74394-3_21
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Constructional Approach of L2 Morphological Processing

Abstract: Following Silva & Clahsen seminal work, psycholinguistic research on L2 morphological processing has mainly adopted a morpheme-based, decompositional dual route approach suggesting that L2 learners have a limited access to morphological representation during processing and consequently rely more on lexical storage (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…Indubitably, sublexical morphemes such as suffixes play a fundamental function in visual word identification. Behavioral evidence has extensively supported the role of morphemes in the recognition of complex words (e.g., Amenta & Crepaldi, 2012;Bonandrini et al, 2023;Giraudo & Voga, 2014;Rastle & Davis, 2008), including experiments where, similar to the present study, suffixes where presented in isolation and under tight visual conditions (masked priming;e.g., Andoni Dunabeitia et al, 2008). This was further corroborated by several neuroimaging studies (e.g., Beyersmann et al, 2021;Davis et al, 2004;Devlin et al, 2004;Gold and Rastle, 2007;Lavric et al, 2012;Lehtonen et al, 2011;Lewis et al, 2011;Pescuma et al, 2022; for a recent review, see Leminen et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…Indubitably, sublexical morphemes such as suffixes play a fundamental function in visual word identification. Behavioral evidence has extensively supported the role of morphemes in the recognition of complex words (e.g., Amenta & Crepaldi, 2012;Bonandrini et al, 2023;Giraudo & Voga, 2014;Rastle & Davis, 2008), including experiments where, similar to the present study, suffixes where presented in isolation and under tight visual conditions (masked priming;e.g., Andoni Dunabeitia et al, 2008). This was further corroborated by several neuroimaging studies (e.g., Beyersmann et al, 2021;Davis et al, 2004;Devlin et al, 2004;Gold and Rastle, 2007;Lavric et al, 2012;Lehtonen et al, 2011;Lewis et al, 2011;Pescuma et al, 2022; for a recent review, see Leminen et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…For instance, Diependaele, Dunabeitia, Morris, and Keuleers (2011), tested pair words with a derivational relationship, the outcome was priming effects for both groups of natives and non-natives. Dal Maso and Giraudo's (2014) work indicated that L2 speakers are sensitive to morphological markers as long as they acquire them. They found that rare affixes did not show priming in their L2 data while frequent and productive affixes were parallel between the L1 and L2 participants.…”
Section: L2 Processing Of Derivational Morphologymentioning
confidence: 99%
“…Previous research on morphological processing has proved that decomposition is not a compulsory processing mechanism applicable to all lexical forms including real complex words, pseudo-morphological words, even nonwords (Giraudo & Dal Maso, 2018). Instead, it depends on the underlying morphological complexity (Pliatsikas et al, 2014) or the interplay of linguistic factors (Bertram et al, 1999).…”
Section: Factors Involved In Morphological Processingmentioning
confidence: 99%
“…The issue of what factors may affect morphological processing has attracted considerable attention, yet existing findings are not consistent to draw a conclusion. Some studies have shown the effects of factors such as formal regularity (Masrai & Milton, 2015;Shi & Chen, 2014), semantic transparency (Marslen-Wilson et al, 1994;Wang & Zhang, 2013;Xu & Taft, 2015;Zhang, 2015Zhang, , 2016, affix productivity (Bertram et al, 1999;Dal Maso & Giraudo, 2014;Lu, 2003;Vannest et al, 2011;Clark, 2014), surface frequency (Dal Maso & Giraudo, 2014;Davies et al, 2016;MacLeod & Kampe, 1996;Masrai & Milton, 2015;Meunier & Segui, 1999), root frequency (Beauvillain, 1996;Yao et al, 2012), stem frequency (Giraudo et al, 2015), and base frequency (Taft, 2004;Xu & Taft, 2015). Productivity refers to the possibility that a word-formation pattern is used to create words.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation